Vitamine A Suplementation for 6-12 Months Baby Toward the Number of Morbidity Rate - Nur Khafidhoh; Agustin Setianingsih; Sri Sumarni (Jurnal LINK, 2014)
The aim of this research is to evaluate the effectiveness of vitamin A for 6 to 12 months baby toward the number of morbidity rate. This was a quasy experimental with posttest case control group design. The total number of sampel was 40 babies age 6 to 12 monts. The data was analised by an independen t-test. The result shows that the illness frequency of baby consumed Vitamin A was 0,55 times less than babies who did not. Baby who consumed less vitamin A has only 1, 8 days of illness, and 6,75 days for babys who did not consume Vitamin A. Babies who consumed vitamin A only encountered 0,7 kinds of diseases, while 2,10 kinds of diseases encountered by non-consumer babies. In conclusion, serving Vitamin A is an effective step in reducing the morbidity for 6 to 12 months babies with a frecuency of illness of p=0,001. Moreover the length of illness period and the kinds of diseases have the same p=0,0001. Health care provider especilly midwives have to encourage women to ensure that the baby is suplemented with itamin A at February and August every year.